2021
DOI: 10.2196/23548
|View full text |Cite
|
Sign up to set email alerts
|

WeChat as a Platform for Baduanjin Intervention in Patients With Stable Chronic Obstructive Pulmonary Disease in China: Retrospective Randomized Controlled Trial

Abstract: Background Pulmonary rehabilitation is a crucial part of the nonpharmacological treatment of stable chronic obstructive pulmonary disease (COPD), but management remains problematic. WeChat could serve as a useful tool in patient management. Baduanjin is a popular exercise in China that is usually applied in pulmonary rehabilitation, which has been confirmed to be effective in improving lung function and life quality. Objective This study aimed to explor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Twenty trials provided an individual rehabilitation setting [ 8 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] while the rest of the trials [ 40 , 41 ] were in a group setting. Two trials [ 8 , 39 ] tested the maintenance effect of the TR intervention for the continuity of care after discharge from the clinic.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty trials provided an individual rehabilitation setting [ 8 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] while the rest of the trials [ 40 , 41 ] were in a group setting. Two trials [ 8 , 39 ] tested the maintenance effect of the TR intervention for the continuity of care after discharge from the clinic.…”
Section: Resultsmentioning
confidence: 99%
“… 19 Another recent clinical trial demonstrated that WeChat PR strategy provided a greater improvement in HRQL, lung function, and showed better adherence. 37 In the current study, we applied WeChat PR maintenance strategy in Group A. The patient-physician communications in this remote model were accomplished via smartphone applications which provided all PR maintenance components to patients and gave feedback or suggestions by clinicians according to uploaded patients’ vital signs during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical trial found that the WeChat app could improve quality of life and lung function and contribute to better adherence. 46 In the current study, SLC participants could share their health information, express their own experiences, encourage each other, and gain access to many medical and health care services. 47 If these patients experience an emergency condition such as AMI or acute heart failure, convenient hospital access helps reduce their waiting time and guarantees timely treatment.…”
Section: Discussionmentioning
confidence: 99%